If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -7x = 2x + 58 Reorder the terms: 13 + -7x = 58 + 2x Solving 13 + -7x = 58 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 13 + -7x + -2x = 58 + 2x + -2x Combine like terms: -7x + -2x = -9x 13 + -9x = 58 + 2x + -2x Combine like terms: 2x + -2x = 0 13 + -9x = 58 + 0 13 + -9x = 58 Add '-13' to each side of the equation. 13 + -13 + -9x = 58 + -13 Combine like terms: 13 + -13 = 0 0 + -9x = 58 + -13 -9x = 58 + -13 Combine like terms: 58 + -13 = 45 -9x = 45 Divide each side by '-9'. x = -5 Simplifying x = -5
| x=0.5 | | 5z-7=13-3z | | s(s-6)=-8 | | 16x=(30x-15)-20 | | 6n^2+2n-140=0 | | b^2+6b-7=0 | | 4c^2+9xy-9y^2= | | -3v+10=40 | | 7p^2-4p=0 | | 16x^2-96x-100=0 | | 3k^2-22k+24=0 | | 2b+9=25 | | 21/3= | | f(6)=7x-20 | | 3a+5=2 | | 5x^2+32x-64=0 | | 4X+3=2(2X+3)-7 | | x+19= | | 6x-10=2x+18 | | (5w+8)(9+w)=0 | | 3z+(-2)=-8 | | 36(16-2.5x)=16(2x-5)+21.6 | | W^3=-13 | | 3z+(-2)=-9 | | 2(7y-4.3)+8=3(2y-0.2) | | 16(x-2)-1=14x+1 | | 4x^3+18x^2-24x=0 | | x^3-4x+3x^2-12=0 | | (7x+9)(5x-6)=0 | | ax^2+4x+2=0 | | 10x^2+24x-18=0 | | -20.02-1.4x=4.5(x+2.5) |